Combined Use of Vinasse and Nitrogen as Fertilizers Affects Nitrification, Ammonification, and Denitrification by Prokaryotes - de Chaves, Miriam Gonçalves; Venturini, Andressa Monteiro; Merloti, Luis Fernando; Barros, Dayane Juliate; Rossetto, Raffaella; Kuramae, Eiko Eurya; Tsai, Siu Mui; Navarrete, Acacio Aparecido (Frontiers in Soil Science, 2021)
A common agricultural practice of combining organic fertilizer vinasse (a liquid residue from sugarcane ethanol production) with mineral nitrogen (N) fertilizer promotes N losses such as greenhouse gas emissions due to the effects of physicochemical changes in soil on the microbiota inhabiting this environment. In this study, we applied microarray GeoChip v.5.0M technology to obtain a better insight into the prokaryotic communities and identify and quantify the N functional gene families associated with the N processes in sugarcane soils without N fertilizer (N0), with urea at 60 kg ha-1 (N60), and with vinasse combined with urea (NV). Soil samples were collected at 7 (T7) and 150 (T150) days after N application, corresponding to maximum and minimum nitrous oxide (N2O) emissions respectively, for molecular and physicochemical analysis. Additionally, the metagenomes of these DNA samples, previously deposited in the MG-RAST server, were accessed to investigate the functions and taxonomic groups associated with selected gene families. The results revealed that 87% of the select gene families were significantly responsive to the fertilizer combined treatment (NV) in the seven days after the application. The most responsive genes and processes were nitrification (with the amoA gene from ammonia-oxidizing Bacteria (AOB) and Archaea (AOA) and hao from Bacteria), ammonification (with gdh and ureC genes from Bacteria and Archaea), and denitrification (with p450nor from Eukarya). The AOA, Nitrosopumilus, and AOB, Nitrosomonas, were the groups with the greatest functions associated with nitrification, as well as a pathogenic Mycobacterium, with denitrification. The results also revealed that under N fertilizers and decreased O2 in soil, the increases in K and P nutrients can promote the growth of the halophile Archaea Natronomonas and the Bacteria Anaeromyxobacter, which can reduce N2O. In conclusion, this typical agricultural fertilization management may favor functional genes and archaeal and bacterial groups associated with N processes that have the potential to reduce environmental damage in tropical sugarcane soils